Assessing effectiveness of teaching practice towards quality preparation of preservice technical teachers - Oladiran Stephen Olabiyi (Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
The study assesses effectiveness of teaching practice towards quality preparation of preservice technical teachers for the world of work considering support received from cooperating teachers vis-à-vis: planning/development of lessons, classroom management/control, professional personality/responsibility, teaching skills, number of periods and challenges confronting preservice teachers, were investigated. The study adopted a descriptive survey research design. Data were obtained using a structured questionnaire from the sample of 82 preservice technical teachers. The collected data were analyzed using mean, standard deviation, independent sample t-test and ANOVA to test hypotheses at 0.05% level of significance. The study found that supports and training have positive impacts on preservice technical teachers with vis-a-vis training domains towards quality preparation. However, the study shows that gender and school type does not influence preservice technical teachers’ perception regards to support and training. Consequently, the study recommended that schools administrators and cooperating teachers should increase acceptability and guidance of preservice teachers, work out modalities with institutions to ensure quality preparation of teachers for the world of work, challenges identified should be taken care of to improve preservice teachers’ competence